A survey of Chinese citizens' perceptions on farm animal welfare. - Xiaolin You (Public Library of Science (PLoS), 2014)
Farm animal welfare has been gradually recognized as an important issue in most parts of the world. In China, domestic animals were traditionally raised in backyard and treated as an important component of family wealth. Industrialization of animal production brings forth the farm animal welfare concerns recently in China, yet the modern concept of animal welfare has not been publicized and a comprehensive recognition on how consumers and farmers perceive animal welfare is lacking. Therefore, we conducted a survey on public opinions toward farm animal welfare in China, based on pigs (including sows, piglets, and fattening pigs), domestic fowls (including layers and broilers) and their products. From 6,006 effective questionnaires approximately two thirds of the respondents had never heard of 'animal welfare'; 72.9% of the respondents claimed that, for the sake of animal derived food safety, human beings should improve the rearing conditions for pigs and domestic fowls; 65.8% of the respondents totally or partly agreed on establishing laws to improve animal welfare; more than half of the respondents were willing, or to some extent willing, to pay more for high-welfare animal products, whereas 45.5% of the respondents were not willing or reluctant to pay more. In summary, farm animal welfare is still in its early stage of development and more efforts are needed to improve the public conception to animal welfare in the process of establishing farm animal welfare standards and legislations in China.